2013
DOI: 10.1186/1471-2172-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Human CD3γ, but not CD3δ, haploinsufficiency differentially impairs γδ versus αβ surface TCR expression

Abstract: BackgroundThe T cell antigen receptors (TCR) of αβ and γδ T lymphocytes are believed to assemble in a similar fashion in humans. Firstly, αβ or γδ TCR chains incorporate a CD3δε dimer, then a CD3γε dimer and finally a ζζ homodimer, resulting in TCR complexes with the same CD3 dimer stoichiometry. Partial reduction in the expression of the highly homologous CD3γ and CD3δ proteins would thus be expected to have a similar impact in the assembly and surface expression of both TCR isotypes. To test this hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In this study, three patients out of four had increased frequencies of TCRγδ T cells and all had expanded NKT-cell populations. An elevation of TCRγδ T cells has been observed in some combined immunodeficiencies such as recombination activating gene 1,2 deficiency ( 21 , 22 ), CD3γ, and CD3δ ( 23 , 24 ), as a consequence of CMV infection or delayed-onset combined immune deficiency with granuloma and/or autoimmunity ( 25 27 ). While the source of the defect in innate-like T cells in GATA2 deficiency is unclear, it is possible that the markedly reduced numbers of antigen presenting cells (DC, monocytes, and B cells) could produce a dysregulated increase of invariant T cells such as TCRγδ and NKT cells ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, three patients out of four had increased frequencies of TCRγδ T cells and all had expanded NKT-cell populations. An elevation of TCRγδ T cells has been observed in some combined immunodeficiencies such as recombination activating gene 1,2 deficiency ( 21 , 22 ), CD3γ, and CD3δ ( 23 , 24 ), as a consequence of CMV infection or delayed-onset combined immune deficiency with granuloma and/or autoimmunity ( 25 27 ). While the source of the defect in innate-like T cells in GATA2 deficiency is unclear, it is possible that the markedly reduced numbers of antigen presenting cells (DC, monocytes, and B cells) could produce a dysregulated increase of invariant T cells such as TCRγδ and NKT cells ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…When surface TCR expression is low, αβ T cells can be identified by the expression of CD4 or CD8αβ (i.e., CD8 bright ) within the lymphoid subset ( 23 ), whereas γδ T cells are identified only by expression of the γδTCR. We have reported that most CD3 + cells within normal DN lymphocytes are γδ T cells ( 34 ), and this may also help in certain TCRID.…”
Section: Lab Tricks To Identify αβ and γδ T Cells In Tcridmentioning
confidence: 99%
“…ENSG00000160654, CD3G, has also been extracted as a candidate biomarker. CD3G has been widely reported to participate in antigen recognition associated biological processes, coupling antigen recognition to specific intracellular signal transduction pathways [ 101 , 102 ]. Encoding a specific protein that can be easily detected by liquid biopsy, CD3G has been confirmed to be differentially expressed, and may be a direct target of different functional microRNA targets different subtypes [ 103 ].…”
Section: Discussionmentioning
confidence: 99%